THE EFFECT OF ENVIRONMENTAL UNCERTAINTY AND TRANSFER PRICING ON TAX AVOIDANCE - Yopie, Santi; Taniono, Meififanny (Universitas Riau, 2024)
The purpose of this study is to examine whether environmental uncertainty and transfer pricing affect manufacturing companies' tax avoidance on the Indonesia Stock Exchange (IDX). Using purposive sampling, 156 manufacturing companies from 2018 to 2021 were selected for this study's sample. Data are analyzed using linear regression using Eviews software version 12. This study implies that the average tax load carried by the sampled companies is modest. On the other hand, this study found that environmental uncertainty does not impact tax avoidance. Meanwhile, transfer pricing has a significant impact on tax avoidance. Most companies, while facing environmental uncertainty, are relatively proficient in upholding their performance, leading to solid earnings consistency without giving much consideration to the amount of taxes they will incur.